The Struggle to Establish Bioentrepreneurship Education Programs: An Australian Perspective - Bridge, Wallace (Technology Transfer and Entrepreneurship (Discontinued), 2017)
The Australian public has long been demanding the implementation of government policies that will lead to profits from Australian know-how remaining in Australia. To achieve this competitiveness in the biotechnology industry, Australia's education system for science students needs to be sufficiently adequate to produce graduates that, are scientifically competent to generate the technology opportunities, have the business acumen to map the commercialisation pathway, and have the entrepreneurial mindset to both drive and enable business success. The problem is that science students at all levels are generally not inherently business minded and most do not realize that they should play an active entrepreneurial role in the translation of their future research findings. As such, it is one thing to design a program to teach business skills and entrepreneurship to science students and scientists and it is another thing to get them to sign up. Since 1999, various education models have been attempted at UNSW to teach business and entrepreneurship to biotechnology students. All have had some success but few have been sustainable due to structural, marketing, funding and political issues. The current Australian Federal Government has launched numerous initiatives aimed at stimulating entrepreneurship in science based industries. New and revised grant funding schemes are obliging universities to become engaged with industry and to encourage entrepreneurship amongst the student body and faculty. Infrastructure and associated funding is being put in place to assist start-ups access funding and launch into global markets. Perhaps the major gap that still needs to be addressed is not the provision of adequate program offerings but the failures in our marketing strategies to effectively engage high school students in the relevance of entrepreneurship to scientific translation and to encourage those who are entrepreneurial minded and interested in science to actually study science at university.
Keywords: economy